Mengidentifikasi Faktor-Faktor Learning Loss pada Pembelajaran Matematika Siswa Kelas VIII - Saputri, Pelia Triangela Indah; Hartati, Sri; Ramadhani, Irma; Aripin, Usman (Jurnal Padegogik, 2024)
Long-term home learning can lead to a decline in students' academic knowledge and skills, resulting in a delay in the learning process known as learning loss. The aim of this study is to investigate the factors influencing the learning outcomes of junior high school students after the Covid-19 pandemic. The research design used is descriptive qualitative. The subjects of this study consist of 120 students. The study employs purposive sampling technique, resulting in 34 research subjects. Data collection methods include interviews, observations, and questionnaires. Three data analysis techniques are utilized: data reduction, data presentation, and conclusion drawing. The study focuses on four issues: preparation for learning, the learning process, learning tools or media, and students' final outcomes. The research findings indicate that the condition of learning loss in eighth-grade students at junior high school is still relatively high. Therefore, it is expected that this research can identify the factors causing the decline in learning among junior high school students with the goal of improving the quality of education